(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This work estimates error for the numerical solution of the diffusion equation using the finitedifference method. To find the numerical approximation of the Diffusion equation, the Explicit centreddifference scheme is explained. The numerical scheme is used to carry out the numerical features oferror estimation. We present the variable separation method to obtain an analytic solution. We create acomputer programme in scientific programming language to implement the finite difference method. Forcomparison, an example is used numerical results are then compared to analytical solutions.